2014
DOI: 10.1007/978-3-662-45526-5_4
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Influence of Electronic Word-of-Mouth on Outbound Tourists’ Visit Intention

Abstract: Abstract. The valence of online user-generated reviews is an increasing important antecedents affecting tourist's decision with the pervasion of Web 2.0 and information and communication technology. The purpose of this study is to explore the influence of electronic word-of-mouth (eWOM) on outbound tourists' intention to visit a destination through a dual-process perspective. A research model was proposed based on the dual-route theory of elaboration likelihood model (ELM) and theory of planned behavior (TPB).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Information (sources) and expectations were also found to be important factors in Chinese tourism to Scandinavia. The initial findings coincided with the literature on China outbound tourism generally, as it was shown that online and/or offline word of mouth were of considerable importance as information sources for Chinese tourists to Scandinavia (Chen, Dwyer, & Firth, ; Wang , ; Yang, Jing, & Nguyen, ). However, the findings showed that unlike China outbound tourists generally, those to Scandinavia knew little about the destination(s) to which they were travelling:
Most of the places in Scandinavia, actually we are not so familiar with (…) I mean, I am not familiar with most of the scenic spots there.
…”
Section: Findings and Discussionsupporting
confidence: 78%
“…Information (sources) and expectations were also found to be important factors in Chinese tourism to Scandinavia. The initial findings coincided with the literature on China outbound tourism generally, as it was shown that online and/or offline word of mouth were of considerable importance as information sources for Chinese tourists to Scandinavia (Chen, Dwyer, & Firth, ; Wang , ; Yang, Jing, & Nguyen, ). However, the findings showed that unlike China outbound tourists generally, those to Scandinavia knew little about the destination(s) to which they were travelling:
Most of the places in Scandinavia, actually we are not so familiar with (…) I mean, I am not familiar with most of the scenic spots there.
…”
Section: Findings and Discussionsupporting
confidence: 78%
“…Numerous studies have been conducted on the impact of e-WOM in the hospitality industry [17], [24]. For instance, Xie et al [25] reported that negative e-WOM is more powerful than positive e-WOM in influencing consumers' booking intentions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of all the factors that influence user behavior when adopting the opinions of other users on this platform, credibility is of a great importance [12], [15]- [17]. Credibility also influences the reputation of a tourism company, which is why it is important for the adoption of e-WOM and for the management of a company's online reputation.…”
Section: Introductionmentioning
confidence: 99%
“…The dependent variables of intention imitated from the TPB are intention to visit an outbound leisure travel destination and the intention to recommend the destination (WOM intention). Prior research has focused on predicting WOM adoption from information receiver's perspective (Cheung et al, 2009;Jin and Phua, 2014;Fang, 2014); few studies are focused on exploring WOM intention from information distributor's perspective (Shih et al, 2013a;Wang, 2014). Thus, this research will address the intention to distribute WOM based on their different routes of perception of travel-related information source.…”
Section: Incorporating Elm With Tpbmentioning
confidence: 99%